Leveraging Digital Literacy for Indonesian Language Learning: Strategies to Enhance High School Students' Writing Skills– Opportunities and Obstacles - E. Sulyati; Kuswara Kuswara (STAI Hubbulwathan Duri, 2025)
The Merdeka Belajar Curriculum in Indonesia prioritizes literacy development, particularly in Indonesian language education, as a means of enhancing students' language proficiency, critical thinking, and sense of national identity. Writing, a key component of this curriculum, requires not only cognitive but also technological competencies. This study employed a descriptive qualitative research design to investigate the role of digital literacy in improving students' writing skills at the high school level. Data were collected through in-depth interviews, participatory observation, and documentation. Findings indicate that digital literacy enhances writing skills by broadening access to information, increasing writing flexibility, and promoting critical thinking. Students showed increased engagement and collaboration when using digital tools. However, implementation challenges persist, including limited technological infrastructure, unequal access to devices, and varying levels of digital competency among educators and learners. Although digital literacy presents a promising avenue for strengthening writing instruction, these benefits can only be fully realized when infrastructural and skill-related barriers are addressed. Digital literacy has significant potential to improve writing skills in Indonesian language education. To ensure its successful integration, a collaborative approach involving schools, educators, and policymakers is essential. This collective effort should focus on creating equitable access to technology and fostering digital competence to support an inclusive and effective digital learning environment.